МЯГКОПЛОДНИК КРИСТМОЛИСТНЫЙ-MALACOCARPUS CRITHMIFOLIUS (RETZ.) C.A.MEY., ВО ФЛОРЕ РЕСПУБЛИКИ КАРАКАЛПАКСТАН - Ажиев, А.Б.; Уснатдинов, Ж.Н.; Юлдашова, Л.М.; Сабирова, Г.Ж. (SCIENCE and SOCIETY, 2023)
The article gives the purpose and objectives of the study, botanical description, and biology of the soft-leaved crithmifolius - Malacocarpus crithmifolius in the Republic of Karakalpakstan. Promising food and ornamental plant for widespread use on saline inconvenient lands and for introduction into culture as a berry plant in the industrial areas of Karakalpakstan. Population: In 2022, 7 cenotic populations of the species were noted (on the eastern of Ustyurt), with a total number of about 200 individuals. The main limiting factors were poor renewal in natural conditions. Economic activity in habitats; damage to bushes, stumping of stems by man. M. crithmifolius reproduces by seeds and vegetatively (layering). It resumes from the stump, takes root by layering (covered with stones or soil), creeping shoots. Propagated by seeds, but in nature a small number of individuals survive self-seeding.
Keywords: reproduction of blackcorn; chemical composition of blackcorn; biology of blackcorn; botanical description of blackcorn; etc